Pengaruh Media Peta Budaya Terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran IPAS Kelas IV SD - Anggraini, Rani; Rahmawati, Ery; Susilo, Tri Achmad Budi (Universitas Negeri Makassar, 2024)
The aim of this research is to find out the influence of cultural map media on critical thinking skills in the material on the norms and customs of my region in grade IV elementary school and to find out students' responses to learning using cultural map media in the material on norms and customs of my region in grade IV elementary school. This research is quantitative research using an experimental approach to test whether treatment has an impact on the researcher's findings. The results of the Hypothesis Test using a comparative test of 2 independent samples obtained a value of 0.000 < 0.05, so it can be concluded that H0 is rejected. Thus it can be said that there is a difference in students' critical thinking abilities between the experimental group and the control group. Because there are significant differences, it can be concluded that there is an influence of cultural map media on critical thinking skills in science subjects. The results of the student's response received a score of 160 with a percentage of 83.33% if conventionalized using the eligibility qualification table, it can be concluded that learning using cultural map media in the science and science subject for class IV elementary school is very good.